Planned mode of birth after previous cesarean section: A structured review of the evidence on the associated outcomes for women and their children in high-income setting - Fitzpatrick, Kathryn E.; Quigley, Maria A.; Kurinczuk, Jennifer J. (Frontiers in Medicine, 2022)
In many high-income settings policy consensus supports giving pregnant women who have had a previous cesarean section a choice between planning an elective repeat cesarean section (ERCS) or planning a vaginal birth after previous cesarean (VBAC), provided they have no contraindications to VBAC. To help women make an informed decision regarding this choice, clinical guidelines advise women should be counseled on the associated risks and benefits. The most recent and comprehensive review of the associated risks and benefits of planned VBAC compared to ERCS in high-income settings was published in 2010 by the US Agency for Healthcare Research and Quality (AHRQ). This paper describes a structured review of the evidence in high-income settings that has been published since the AHRQ review and the literature in high-income settings that has been published since 1980 on outcomes not included in the AHRQ review. Three databases (MEDLINE, EMBASE, and PsycINFO) were searched for relevant studies meeting pre-specified eligible criteria, supplemented by searching of reference lists. Forty-seven studies were identified as meeting the eligibility criteria and included in the structured review. The review suggests that while planned VBAC compared to ERCS is associated with an increased risk of various serious birth-related complications for both the mother and her baby, the absolute risk of these complications is small for either birth approach. The review also found some evidence that planned VBAC compared to ERCS is associated with benefits such as a shorter length of hospital stay and a higher likelihood of breastfeeding. The limited evidence available also suggests that planned mode of birth after previous cesarean section is not associated with the child’s subsequent risk of experiencing adverse neurodevelopmental or health problems in childhood. This information can be used to manage and counsel women with previous cesarean section about their subsequent birth choices. Collectively, the evidence supports existing consensus that there are risks and benefits associated with both planned VBAC and ERCS, and therefore women without contraindications to VBAC should be given an informed choice about planned mode of birth after previous cesarean section. However, further studies into the longer-term effects of planned mode of birth after previous cesarean section are needed along with more research to address the other key limitations and gaps that have been highlighted with the existing evidence.